ANALISIS KESEHATAN DAN KESELAMATAN KERJA BAGIAN PRODUKSI ROTI DENGAN MENGGUNAKAN METODE HAZARD AND OPERABILITY Studi Kasus : UMKM LAZIZA BAKERY & CAKE - Wahyu Adhi Prasetyo; Andung Jati Nugroho (CV. ALIM'SPUBLISHING, 2023)
UMKM Laziza Bakery & Cake is a company that produces various types of bread. Based on work accident data collection in this study, the company was faced with several problems in the production department, one of which was that the hands were exposed to heat from the oven. This happens due to several factors, including human factors and machine factors. the design of recommendations or proposed improvements is made based on the hazard (potential hazard) that occurs. The Hazard And Operability method aims to overcome this problem, with the hope that it can reduce the risk of work accidents at the UMKM Laziza Bakery & Cake. We can see that the hazard sources for the production machine category from the 6 production machines used have a medium risk level of 4 on mixer machines, mixing machines, packing machines, and cutting machines. For hazard sources for facility design, there are 2 factors that have a medium risk level, namely PPE posters and equipment arrangement. Then for the source of hazard the attitude of workers has a risk level extreme with the category of potential hazards caused by potential hazards (hazard) extreme risk and worksheets in the use of PPE in the work area so that workers can immediately read what are the potential hazards they will experience if not using PPE